Chalinus albitibialis, a new species of Orussidae (Insecta, Hymenoptera) from Morocco - Vilhelmsen, Lars (Zootaxa, 2005)
Chalinus albitibialis n. sp. is described and illustrated. It differs from all other members of the genus by possessing an extensive white area on the hind tibia. It is the first record of the genus from North Africa. The phylogenetic position of the new species relative to other members of Chalinus and the implications for the biogeography of the genus are discussed.